A history of Judaism. - Silver, Daniel Jeremy; Martin, Bernard, 1928- (New York : Basic Books, 1974)
Issued in a case.
Includes bibliographies and indexes. v.1 Silver, D. J. From Abraham to Maimonides. v.2 Martin, B. Europe and the New World
Keywords: Judaism -- History